Implikasi Model-Model Kurikulum dan Perencanaan PAK dalam Pertumbuhan Iman Pemuda di Gereja HKBP Sipeapea - Darwin Sibarani; Andar Gunawan Pasaribu (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This study aims to analyze the implications of curriculum models and the planning of Christian Religious Education in the spiritual growth of youth at the HKBP Sipeapea Church. The research employs a qualitative descriptive method with approaches including literature review, in-depth interviews, participatory observation, and qualitative data analysis. The findings reveal that effective PAK planning, which is relevant and responsive to the needs of the youth, plays a crucial role in their spiritual development. The curriculum models used should incorporate diverse methods such as group discussions, spiritual retreats, and church service activities. The study indicates that by designing an engaging curriculum that addresses the challenges youth face today, the church can enhance the quality of faith and involvement of young people in spiritual activities. Moreover, regular evaluation is important to ensure the curriculum remains relevant and adaptable to changing times. This research is expected to contribute to the development of more effective PAK planning, especially for the youth at the HKBP Sipeapea Church.